POSITIONING DIGITAL LITERACY IN MODERN PESANTREN: TEACHERS’ PERCEPTIONS AND EDUCATIONAL IMPLEMENTATION - Marnang Saing; Hadi Saputra Panggabean; Yunus; Nafiza Fadia Anwar (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Digital literacy has become an essential competence in modern education; however, its implementation in pesantren presents distinctive dynamics, particularly when institutions restrict students’ access to digital devices while simultaneously encouraging teachers to master digital literacy. This study aims to examine how digital literacy is positioned, perceived, and implemented in the learning process at Pesantren Ar-Raudlatul Hasanah as one of Indonesia’s modern pesantren. Employing a qualitative approach with a case study design, data were collected through semi-structured interviews, non-participant observation of classroom practices and pesantren activities, and analysis of institutional documents. The data were analyzed using thematic analysis to identify relevant patterns and key themes. The findings reveal that digital literacy in the pesantren is positioned primarily as a learning resource mediated by teachers rather than as an individual competence freely accessible to students. Teachers’ perceptions of digital literacy are reflective and selective, shaped by moral and scholarly responsibility, concern for students’ ethical conduct (adab), and apprehension regarding the negative impacts of the digital environment. In terms of implementation, digital literacy is applied in a limited and functional manner through teachers’ use of digital learning media, basic computer courses for students, cultural and extracurricular pesantren activities, and the digitalization of institutional administrative systems. This study concludes that the pesantren has developed a contextual and ethically grounded model of digital literacy, in which technology functions as a supportive educational tool without displacing core values, scholarly authority, or the primary goal of students’ character formation. These findings contribute empirical insights to the growing body of research on digital literacy within the context of Islamic education, particularly in modern pesantren